Impact of COVID-19 on the quality of higher education in Pakistan: students’ perspective - Maham Khalid; Aamir Sarwar; Sardar Ahmad; Bushra Rehman (Cogent Social Sciences)
The research aimed to explore how COVID-19 impacted higher education quality from students’ perspective and emphasized the need for faculty-student training in online teaching. Data from Lahore’s public and private university students were collected through a detailed questionnaire. Statistical tools such as Excel, SPSS 23.0, and Smart-PLS 3.2 were used for analysis. COVID-19’s effect was the independent variable, higher education quality as the dependent variable, and technology training needs acted as a mediator between them. Results indicated that faculty-student training significantly mediated the relationship between COVID-19 impact and education quality. The type of university was a noteworthy moderator between COVID-19’s impact and faculty-student training needs, suggesting moderated mediation. Multi group analysis (MGA) involving male and female students from public and private institutions showed statistically significant findings in all groups, with partial mediation between the independent and dependent variables. This study benefits educators’ understanding of COVID-19’s impact on higher education and its effect on teacher-student training. Addressing challenges highlighted could lead to a promising future for eLearning, increasing opportunities for wider participation. Institutions can provide effective online and on-campus programs regardless of COVID-19 compliance.